New alumni EXperiences of Training and independent Unsupervised Practice (NEXT-UP): protocol for a cross-sectional study of early career general practitioners. Issue 5 (30th May 2019) - Magin, Parker; Moad, Dominica; Tapley, Amanda; Holliday, L; Davey, Andrew; Spike, Neil; FitzGerald, Kristen; Kirby, Catherine; Bentley, Michael; Turnock, Allison; van Driel, Mieke L; Fielding, Alison
Abstract : Introduction: General practice in Australia, as in many countries, faces challenges in the areas of workforce capacity and workforce distribution. General practice vocational training in Australia not only addresses the training of competent independent general practitioners (GPs) but also addresses these workforce issues. This study aims to establish the prevalence and associations of early career (within 2 years of completion of vocational training) GPs' practice characteristics; and also to establish their perceptions of utility of their training in preparing them for independent practice. Methods and analysis: This will be a cross-sectional questionnaire study. Participants will be former registrars ('alumni') of three regional training organisations (RTOs) who achieved general practice Fellowship (qualifying them for independent practice) between January 2016 and July 2018 inclusive. The questionnaire data will be linked to data collected as part of the participants' educational programme with the RTOs. Outcomes will include alumni rurality of practice; socioeconomic status of practice; retention within their RTO's geographic footprint; workload; provision of nursing home care, after-hours care and home visits; and involvement in general practice teaching and supervision. Associations of these outcomes will be established with logistic regression. The utility of RTO-provided training versus in-practice training in preparing the early career GP for unsupervised post-Ffellowship practice in particular aspects of practice will be assessed with χ 2 tests. Ethics and dissemination: Ethics approval is by the University of Newcastle Human Research Ethics Committee, approval numbers H-2018-0333 and H-2009-0323. The findings of this study will be widely disseminated via conference presentations and publication in peer-reviewed journals, educational practice translational workshops and the GP Synergy Research subwebsite.